Editorial: Teaching and Learning for Sustainable Futures - Jared McDonald; Eleanor Bernard; Zachary Simpson (University of Johannesburg, 2024)
In this editorial, the guest editors and SOTL4theSouth conference organisers reflect on the significance of the theme of the conference and special issue, and present an overview of the papers included.